Evaluation of the physical workload in coffee production: biomechanical and physiological aspects - Barbosa, Marco Antonio Gomes; Abrahão, Roberto Funes; Tereso, Mauro José Andrade; Lima, Renato Ribeiro; Chih, Liu Ying (Coffee Science - ISSN 1984-3909, 2015)
The main objective of this research was the assessment of the physical workload of farm coffee workers from southern Minas Gerais, Brazil. Twelve workers were reconded and their heart rate monitored during one hour execution of five different tasks, both on flat and sloping ground. The assessment of body postures adopted and the actions performed were achieved through the “Captiv” software. We attempted to correlate the results of the assessments and interpret them in the light of the observation of the activities of the workers. The most significant cardiovascular demands occurred in subtasks of foliar and manual fertilization, classifying them as moderate work. Harvesting and thinning were the subtasks that appeared to have the greatest variability of postural combinations: the harvest due to the variety of operating actions; the thinning, although only one relevant operational action, due to the very nature of the task. Either the cardiovascular or the biomechanical indicators revealed no statistically significant differences between the subtasks carried by workers in conditions of flat and sloping ground.